Wyznaczanie Parametrów Pewnego Nieliniowego Modelu Reologicznego - A. Jakowluk; M. Czech; J. Kobyłko (Engineering Transactions, 1970)
In this paper, an eight-parameter mechanical nonlinear rheological model is considered with connection in series of: 1) Hook’s body; 2) Kelvin-Voigt’s body; 3) an elasto-plastic body (parallel connection of a nonlinear body and St. Venant’s body); 4) visco-plastic reinforces by a parallel connection of a nonlinear damper and a slide of a dry friction type with pressure dependent on the time and strain for the realization of the first period of creeping characterized by reinforcement, and finally with surface of dry friction with constant pressure for the realization of the second period of creeping. The parameters and characteristics of the nonlinear elements in the proposed model are determined on the basis of the results of experimental studies of creeping tests for an aluminium alloy of Al-Mg-Si (PA4). Good agreement is shown by a comparison made also between the creeping curves determined experimentally and those obtained from analysis of the model with determined parameters and characteristics. The model suggested is quite universal, since it may be utilized for the description of the creeping of all metals and their alloys in the range of very small, large and very large deformations.